In Silico Docking Analysis for Viral Protein - Hemagglutinin-Neuraminidase against the Synthetic Drugs For Human Parainfluenza Virus 3 - AATHI MUTHU SANKAR; PIRAMANAYAGAM SHANMUGHAVEL (International Journal of Pharma and Bio Sciences, 2010)
Hemagglutinin-Neuraminidase (HN) protein is a multifunctional protein responsible for attachment to receptors containing Sialic acid, neuraminidase (NA) activity, and the promotion of the fusion protein. The cell membrane fusion of hemagglutinin-neuraminidase protein and F protein interaction regulation is remaining not clear. This work investigates the binding and entry of the cells of parainfluenza virus type 3, focusing on how the receptorbinding molecule triggers the fusion process. We have used computational methods to find the ligand having best interaction with hemagglutinin-neuraminidase protein. HN protein interactions with the drug namely Amantadine, Rimantadine, Oseltamivir and Zanamivir were studied, in which the best drug interaction with the receptor was confirmed by binding energy, number of hydrogen bond formed and Inhibitory constant result given by Autodock 4. Finally, the conformation result shows that Zanamivir has the maximum hydrogen bond formed and lowest binding energy with the receptor.